Faktor-faktor yang mempengaruhi konservatisme akuntansi - Maria Oktavia Elizabeth Sinambela; Luciana Spica Almilia (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2018)
This study aims to test the effects of firm size, firm risk, capital intensity, taxes, audit committees, managerial ownership, and litigation risk on accounting conservatism. This research uses secondary data from the Indonesian Stock Exchange and Yahoo Finance for daily stock price data. This study analyzes the data from 192 observations using descriptive statistics, a test of classical assumption, and multiple regression analysis. The results indicate that firm size, firm risk, litigation risk, debt covenant, audit committees, managerial ownership do not affect accounting conservatism. However, taxes and capital intensity negatively affect accounting conservatism.